2015
DOI: 10.1002/pssb.201451711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a fast diffusing oxygen species in silicon based on the generation rate of thermal donors

Abstract: Oxygen out-diffusion profiles reported at low temperature (400-500 8C) show a long-range oxygen migration. By the present analysis, the near-surface oxygen loss observed in these experiments is found to be well consistent with the known generation rate of thermal donors (TDs). Accordingly, the fastdiffusing oxygen species (FDS)responsible for the long-distance oxygen diffusionis a relatively large oxygen cluster (most likely, O 6 ) belonging to the TD family. The model developed here accounts for a persistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…7. Recently, it has been shown that faster diffusing oxygen complexes [31] other than dimers, as deciphered from dislocation locking experiments [26], can be present at 400-500 1C anneals. Therefore, the effective diffusivity of oxygen at these temperatures can be higher than the values predicted by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…7. Recently, it has been shown that faster diffusing oxygen complexes [31] other than dimers, as deciphered from dislocation locking experiments [26], can be present at 400-500 1C anneals. Therefore, the effective diffusivity of oxygen at these temperatures can be higher than the values predicted by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Such clusters are, for instance, the various VO n and generally V n O m defects as well as carbon-oxygen related defects such as C i O i (Si I ) n centers. Additionally, at ~450 °C O atoms start to diffuse in the Si lattice and begin to aggregate [10,104] forming initially thermal donors (TDs) and at a later temperature stage O precipitates. All these processes require the involvement of O, which is reflected in the decrease of O concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Oxide precipitates in RTA wafers are normally produced by two-step annealing, 800 + 1000 o C. The density profile N(z) mimics [2,14] the RTAinstalled and Pt-monitored profile of slow vacancies C s (z), according to a cubic dependence: N ~ C s 3 . The density profiles of a good depth resolution have been reported [17] for several T RTA (1280, 1260 and 1240 o C, in Ar or N 2 ambient) and for several cooling rates q (70, 50 and 25 K/s) used after holding at T RTA .…”
Section: Vacancy-controlled Depth Profiles Of Oxide Precipitate Densitymentioning
confidence: 99%
“…Silicon vacancies have been concluded [1,2] to exist in several structural forms strongly differing in the diffusivity D V and the equilibrium concentration C Ve . Three basic vacancy species appear to exist [2].…”
Section: Introduction: Multiple Vacancy Speciesmentioning
confidence: 99%
See 1 more Smart Citation